NIAT MAHASISWA UNTUK BERWIRUSAHA PADA PERGURUAN TINGGI SWASTA DAN NEGERI DI MANOKWARI - Rintar Agus Simatupang; Rinto Patadungan; Deasy Novita Emelia Frisa May (Jurnal Riset Manajemen dan Bisnis, 2015)
This study aims to analyzethe factors that affect a student's intention to entrepreneurship. Sample size were 276 respondents. Respondents this study were students who have taken entrepreneurship courses. The method of analysis used in the study were factor analysis and multiple linear regression. Based on the analysis, this study concluded that student achievement motivation was most influence to entrepreneurship. Then based onthe results ofmultiple linear regression analysis concluded tha tthe factor influencing student intention to entrepreneurship was the locus of control for UNIPA respondents, where as self-efficacy factor was for STIE Mah-Eisa and ISTI Manokwari respondents. Keywords: Achievement motivation, Risk taker, Desire for independent, Locus of control, Self efficacy, Innovation, intention.